Cerium oxide polishing particles and polishing slurry composition

By using a modifier and pH adjuster to treat cerium oxide polishing particles in the polishing slurry, the problem of nano cerium oxide particles aggregation in the polishing slurry composition is solved, and efficient polishing rate and dispersion are achieved, reducing the polishing film Quality defects and scratches.

CN115895595BActive Publication Date: 2024-12-31KC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211037938.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-08-30
Filing Date
2022-08-26
Publication Date
2024-12-31
Estimated Expiration
2042-08-26

AI Technical Summary

Technical Problem

The existing polishing slurry compositions cannot selectively polish the silicon oxide film, silicon nitride film and polysilicon film, and there are problems such as slow polishing speed, defects and scratches, and nano cerium oxide particles are prone to agglomeration during the synthesis process, resulting in Low dispersion.

Method used

By adding a modifier to the cerium oxide polishing particles, the aggregation ratio of the particles is controlled to be between 1.5 and 2.5, surface modification is performed using nonionic compounds and polysaccharides to prevent particle aggregation, and nano cerium oxide polishing with uniform dispersion is prepared. Particles and a pH adjuster is added to the polishing slurry to maintain good dispersion.

Benefits of technology

The monodispersibility of the cerium oxide polishing particles and the excellent dispersibility of the polishing slurry composition are achieved, and the polishing rate is improved and defects and scratches of the polishing film are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003818639980000021
    Figure BDA0003818639980000021
  • Figure BDA0003818639980000041
    Figure BDA0003818639980000041
  • Figure BDA0003818639980000091
    Figure BDA0003818639980000091
Patent Text Reader

Abstract

The present invention relates to cerium oxide polishing particles and a polishing slurry composition, and more specifically, to cerium oxide polishing particles and a polishing slurry composition comprising cerium element and a modifier, and satisfying an aggregation rate calculated by a relationship between primary particle size and secondary particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to nano cerium oxide polishing particles and a polishing slurry composition comprising the nano cerium oxide polishing particles. Background Art

[0002] The chemical mechanical polishing (CMP) process is achieved by applying a slurry containing polishing particles to a substrate and using a polishing pad mounted on a polishing device. At this time, the polishing particles are subjected to pressure from the polishing device to mechanically polish the surface, and the chemical components contained in the polishing slurry composition react chemically with the substrate surface, thereby chemically removing the surface portion of the substrate.

[0003] Generally, the types of polishing slurry compositions vary according to the types and characteristics of the objects to be removed. Among them, the polishing slurry compositions used for selectively removing specific polishing films are very diverse, but recently, in the structure of semiconductor devices, a slurry composition that can simultaneously polish silicon oxide films, silicon nitride films, and polycrystalline silicon films is required. However, the existing slurry compositions cannot selectively polish silicon oxide films, silicon nitride films, and polycrystalline silicon films, and there are problems such as failure to obtain the desired polishing speed, generation of defects, scratches, and generation of agglomerations due to low dispersion stability. In addition, when the cerium oxide particles are angular grain shapes and have a wide particle size distribution, micro scratches will inevitably be generated on the polycrystalline silicon film. In addition, in order to improve the defects and scratches of the polishing film quality and to improve the depressions and erosions in the pattern, it is necessary to apply small particles, and this demand is increasing.

[0004] The cerium oxide nanoparticle synthesis technology (Rhodia, patent 10-1139110) consists of the following steps: adding alkali to a cerium salt to obtain a precipitate; heat-treating the obtained precipitate under an inert atmosphere; and acidifying and washing the medium obtained by the heat treatment to obtain a suspension. The disadvantage of the cerium oxide nanoparticles prepared in the above manner is that the precipitate obtained by adding alkali will cause the particles to agglomerate due to its pH, and these agglomerates are difficult to be crushed again by acidification and washing.

[0005] In the patent using nano-cerium oxide particles (HITACHI Corporation, Patent No. 10-0512134), the primary particle size of the particles is small, but the secondary particle size is large.

[0006] In order to disperse nanoparticles, various processes or chemical additions and treatments are required. Although the nanoparticles have a nanoscale size during the synthesis process, they will aggregate in the aqueous solution, resulting in an increase in particle size. The smaller the particle size, the more intense the aggregation phenomenon, and the aggregated particles are difficult to disperse again. Therefore, it is necessary to provide cerium oxide nanoparticles and polishing slurry compositions comprising the same that prevent aggregation between particles and maintain good dispersibility. Summary of the invention

[0007] Technical issues to be solved

[0008] The present invention solves the above-mentioned problems and provides a polishing slurry composition which can suppress aggregation into secondary particles, thereby providing nano-cerium oxide polishing particles with uniform dispersion, and improving the dispersion and polishing rate of the polishing film.

[0009] However, the technical problems to be solved by the present invention are not limited to the above-mentioned subjects, and other unmentioned subjects will be clearly understood by ordinary technicians in this field through the following description.

[0010] Technical solutions to the problem

[0011] According to an embodiment of the present invention, a cerium oxide polishing particle includes: a cerium element; and

[0012] The modifier has an aggregation ratio (A) of 1.5 to 2.5 based on the following formula 1:

[0013] [Formula 1]

[0014] A=[secondary particle size] / [primary particle size]

[0015] In formula 1, the primary particle size is the r value of formula 2,

[0016] The secondary particle size is a value measured by a dynamic light scattering (DLS) method;

[0017] [Formula 2]

[0018]

[0019] In Formula 2, S0 is the specific surface area, r is the radius of the particle, and p is the density of the substance.

[0020] According to one embodiment of the present invention, the specific surface area (BET) of the polishing particles is 31 m 2 / g or above.

[0021] According to an embodiment of the present invention, the primary particle size according to Formula 2 is less than 25 nm.

[0022] According to an embodiment of the present invention, the secondary particle size of the polishing particles is 5 nm to 50 nm.

[0023] According to one embodiment of the present invention, the density of the polishing particles is 6.7 g / cm 3 Up to 7.7g / cm 3 .

[0024] According to an embodiment of the present invention, the concentration of the modifier included is 0.01M to 1M.

[0025] According to an embodiment of the present invention, the molar ratio of the cerium element to the modifier is 1:0.1 to 1:1.

[0026] According to an embodiment of the present invention, the modifier includes at least any one selected from the group consisting of non-ionic compounds and polysaccharides.

[0027] According to one embodiment of the present invention, the non-ionic compound includes at least one selected from the group consisting of polyethylene glycol (PEG), polypropylene glycol (PPG), polyvinyl pyrrolidone (PVP), polyglycerol, polyvinyl alcohol (PVA), ethylene oxide-propylene oxide copolymer, polyethylene-propylene copolymer, polyalkyl oxide, polyoxyethylene ether (PEO), polyethylene oxide and polypropylene oxide.

[0028] According to one embodiment of the present invention, the polysaccharide includes at least one selected from the group consisting of dextran, dextrin, maltodextrin, cyclodextrin, amylodextrin, glycogen and inulin.

[0029] According to one embodiment of the present invention, it relates to a polishing slurry composition including the cerium oxide polishing particles of the present invention.

[0030] According to an embodiment of the present invention, the polishing particles are 0.01 wt % to 5 wt % of the slurry composition.

[0031] According to one embodiment of the present invention, a pH adjuster is further included.

[0032] According to one embodiment of the present invention, the pH adjuster includes an acidic substance, and the acidic substance includes at least one selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, nitrous acid, persulfuric acid, sulfurous acid, hyposulfurous acid, boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, superphosphoric acid, perchloric acid, chlorous acid, hypochlorous acid, bromic acid, bromic acid, hypobromous acid, perbromic acid, iodic acid, hypoiodous acid, periodic acid, hydrogen fluoride, boron trifluoride, tetrafluoroboric acid, hydrofluoric acid, formic acid, malonic acid, maleic acid, oxalic acid, adipic acid, citric acid, acetic acid, propionic acid, fumaric acid, salicylic acid, pimelic acid, benzoic acid, succinic acid, phthalic acid, butyric acid, glutaric acid, glutamic acid, glycolic acid, lactic acid, aspartic acid, tartaric acid, and their respective salts.

[0033] According to one embodiment of the present invention, the pH value of the polishing slurry composition is 2 to 11.

[0034] According to one embodiment of the present invention, the polishing slurry composition has a positive zeta potential.

[0035] Effects of the Invention

[0036] The present invention provides polishing particles, which obtain a large proportion of as-prepared particles with almost monodispersity during synthesis, and provides a polishing slurry composition including the polishing particles. The polishing particles or the polishing slurry composition have excellent dispersibility through primary dispersion and provide excellent polishing rate. DETAILED DESCRIPTION

[0037] The embodiments of the present invention are described in detail below. When describing the present invention, when it is considered that the specific description of the relevant known functions or structures will unnecessarily confuse the gist of the present invention, the detailed description thereof will be omitted. In addition, the terms in this specification are used to appropriately describe the preferred embodiments of the present invention, which may vary according to the intention of the user, operator or the conventions in the technical field to which the present invention belongs. Therefore, the definition of terms should be based on the overall specification content.

[0038] In the entire specification, when it is stated that a component is “on” another component, it includes not only a case where one component is in contact with the other component but also a case where another component exists between the two components.

[0039] In the entire specification, when it is stated that a part “includes” a certain constituent element, it means that other constituent elements may be further included, rather than excluding other constituent elements.

[0040] The cerium oxide polishing particles and the polishing slurry composition will be specifically described below with reference to examples. However, the present invention is not limited to these examples.

[0041] The present invention relates to cerium oxide polishing particles. According to one embodiment of the present invention, the cerium oxide polishing particles may include cerium element and a modifier.

[0042] In the present invention, the cerium oxide is cerium oxide or cerium (IV) oxide. According to an embodiment of the present invention, the particle aggregation ratio (Aggregate Ratio) of the cerium oxide polishing particles based on the following formula 1 can satisfy 1.5 to 2.5.

[0043] To measure the dispersibility of particles, the particle aggregation rate can be used to predict the primary particle size of the particles through BET analysis, which analyzes the specific surface area of ​​the particles. Since the synthesized nanoparticles are close to spherical, the correlation between the specific surface area and the primary particle size of the particles can be calculated by the following formula (2).

[0044] The particle aggregation rate is defined as the ratio of the primary particle size of the calculated particles to the secondary particle size calculated by dynamic light scattering (DLS) analysis. When included in the above range, the cerium oxide polishing particles are defined as uniformly dispersed particles having almost monodisperse characteristics.

[0045] In the polishing slurry composition, the existing nanoparticle dispersion requires multiple processes or chemical additions, but the cerium oxide polishing particles of the present invention can provide dispersibility without these processes and chemical additions, and help to improve the polishing rate of the polishing slurry composition.

[0046] [Formula 1]

[0047] A=[secondary particle size] / [primary particle size]

[0048] In Formula 1, the primary particle size is the r value of the following Formula 2, and the secondary particle size is a value measured by a dynamic light scattering (DLS) method.

[0049] [Formula 2]

[0050]

[0051] (In Formula 2, S0 is the specific surface area, r is the radius of the particle, and p is the density of the substance.)

[0052] For example, the primary particle size calculated by BET analysis and the secondary particle size obtained by DLS particle size analysis are substituted into Formula 1. When the value of Formula 1 satisfies the above range, it can be defined as monodisperse particles. When particle aggregation occurs, the value of Formula 1 will exceed 2.5. When applied to the polishing slurry composition, the polishing rate of the polishing film will be reduced, resulting in defects such as scratches.

[0053] For example, to obtain the value of Formula 1, the two measurement methods can apply the same dispersion process and apply the same energy for dispersion measurement. For example, the particles are dispersed under the same conditions such as speed (RPM), bead size, time, etc. during the grinding process, and the BET specific surface area and particle size are analyzed, and the relevant values ​​are brought into Formulas 1 and 2.

[0054] As an example of the present invention, the preparation method of the cerium oxide polishing particles is not limited, as long as it is a preparation method of metal oxide particles known in the technical field of the present invention, preferably hydrothermal synthesis, sol-gel method, precipitation method, coprecipitation method, hydrothermal synthesis, filtration method, aging method, spray drying method, thermal evaporation method, etc., and can be prepared using trivalent cerium precursors such as cerium nitride, cerium acetate and cerium sulfonate. The particles synthesized by the above method can have a nanometer size.

[0055] For example, the primary particle size of the cerium oxide polishing particles may be less than 25 nm; 1 nm to 25 nm; or 2 nm to 20 nm, and the secondary particle size of the cerium oxide polishing particles may be 5 nm to 50 nm; or 10 nm to 40 nm. When included in the particle size range, the dispersion stability in the polishing composition is excellent, and the performance degradation can be prevented during a long polishing process, thereby improving the polishing rate.

[0056] As an example of the present invention, the cerium oxide polishing particles are surface-modified by a nonionic compound in the synthesis process, thereby preventing aggregation between particles to prevent aggregation into secondary particles, thereby providing a particle dispersion at or close to a monodisperse level, which can maintain particle dispersion in the polishing slurry composition and improve the polishing rate. For example, the nonionic compound is a compound having nonionic properties in an aqueous solution state, and in the synthesis process of the cerium oxide particles, the nonionic compound is used as a template, thereby utilizing the steric effect between particles to provide particles with good dispersion, and during the synthesis, a steric effect is given between particles to inhibit aggregation between particles.

[0057] As an example of the present invention, the specific surface area of ​​the cerium oxide polishing particles is 31m 2 / g or more; 40m 2 / g or more; 31m2 / g to 200m 2 / g; or 40m 2 / g to 150m 2 / g, when included in the above specific surface area range, it is possible to fully ensure the area of ​​the contact portion between the polishing object film and the polishing object film, provide a high level of polishing speed, and reduce surface scratches and depressions of the polishing object film. The above specific surface area can be measured using the BET (Brunauer-Emmett-Teller) method. For example, it can be measured using a porosimetry analyzer (Porosimetry analyzer; Japan Bell Company, Belsorp-II mini) using the BET six-point method through a nitrogen adsorption method.

[0058] As an example of the present invention, the polishing particles may have a particle size of 6.7 g / cm 3 Up to 7.7g / cm 3 density.

[0059] According to an embodiment of the present invention, the modifier may be included in a concentration of 0.01M to 1M. Within the above range, the participation rate of the polishing particles in the polishing process may be increased, thereby improving the polishing rate.

[0060] As an example of the present invention, the molar ratio of the cerium element to the modifier can be 1:0.1 to 1:10; or 1:0.5 to 1:5.

[0061] As an example of the present invention, the cerium oxide polishing particles are prepared by mixing a trivalent cerium precursor and the modifier, and the molar ratio of the trivalent cerium precursor to the modifier can be 1:0.1 to 1:10; or 1:0.5 to 1:5.

[0062] As an example of the present invention, the modifier may include at least one selected from the group consisting of nonionic compounds and polysaccharides.

[0063] As an example of the present invention, the nonionic compound may include at least one selected from the group consisting of polyethylene glycol (PEG), polypropylene glycol (PPG), poly(isopropylene glycol), polybutylene glycol, polyvinyl pyrrolidone (PVP), polyglycerol, polyvinyl alcohol (PVA), polyoxyethylene methyl ether, polyethylene oxide-propylene oxide copolymer, poly(ethylene glycol)-terminated poly(propylene glycol) (PEG-PPG-PEG block copolymer), polyethylene-propylene copolymer, polyalkyl oxide, polyoxyethylene ether (PEO), polyethylene oxide and polypropylene oxide.

[0064] As an example of the present invention, the weight average molecular weight of the nonionic compound is 3000 or less; 2500 or less; or 2000 or less, or 100 or more; 200 or more; or 300 or more.

[0065] As an example of the present invention, the polysaccharide is a polymer carbohydrate molecule composed of a long chain of monosaccharide monomers linked by glycosidic bonds, for example, it may include at least one selected from the group consisting of dextran, dextrin, maltodextrin, cyclodextrin (e.g., α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin), amylodextrin, glycogen and inulin.

[0066] The present invention relates to a polishing slurry composition comprising the cerium oxide polishing particles of the present invention, and further comprising a pH adjuster.

[0067] According to one embodiment of the present invention, the cerium oxide polishing particles included in the polishing slurry composition are 0.01 to 5 wt %; 0.05 to 2 wt %; or 0.05 to 1 wt %. When the content of the polishing particles is less than 0.01 wt %, a high level of polishing rate cannot be achieved, and when it exceeds 5 wt %, the dispersion stability of the polishing particles is low, defects are increased, and the effect of reducing the depression cannot be achieved.

[0068] According to an embodiment of the present invention, the pH adjuster may include an acidic substance, and the acidic substance includes at least one selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, nitrous acid, persulfuric acid, sulfurous acid, hyposulfuric acid, boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, superphosphoric acid, perchloric acid, chlorous acid, hypochlorous acid, bromic acid, bromic acid, hypobromous acid, perbromic acid, iodic acid, hypoiodous acid, periodic acid, hydrogen fluoride, boron trifluoride, tetrafluoroboric acid, hydrofluoric acid, formic acid, malonic acid, maleic acid, oxalic acid, adipic acid, citric acid, acetic acid, propionic acid, fumaric acid, salicylic acid, pimelic acid, benzoic acid, succinic acid, phthalic acid, butyric acid, glutaric acid, glutamic acid, glycolic acid, lactic acid, aspartic acid, tartaric acid, and their respective salts. For example, an appropriate amount of the pH adjuster is used so that the pH of the polishing slurry composition is 2 to 11, preferably, the pH is adjusted to 4 to 7.

[0069] According to an embodiment of the present invention, the polishing slurry composition has a positive zeta potential in the pH range of 2 to 11, for example, 10 mV to 100 mV.

[0070] According to one embodiment of the present invention, the polishing slurry composition is dispersed using a particle dispersing device known in the technical field of the present invention, for example, homogeneous mixing, ball milling, grinding, ultrasonic dispersion, etc. can be used.

[0071] According to one embodiment of the present invention, the polishing slurry composition can be used in a CMP polishing process of a semiconductor wafer including at least one of a silicon nitride film, a silicon oxide film, a polysilicon film, and a silicon film. The polishing slurry composition can be used in a process of removing a silicon oxide film at a high polishing rate, or in a process of stopping polishing a polysilicon film or a silicon nitride film while removing a silicon oxide film at a high polishing rate. In the polishing process, the polishing rate for the silicon oxide film can be to

[0072] Hereinafter, the present invention will be described in more detail by way of examples, but the following examples are only for illustrative purposes and are not intended to limit the scope of the present invention.

[0073] Example 1

[0074] A trivalent cerium precursor (0.1 M) and polyethylene glycol (weight average molecular weight: 600, 0.05 M) as a nonionic compound were added, and then an aqueous ammonia solution (0.3 M) was added, and the mixture was stirred at 900 rpm for 4 hours to synthesize cerium oxide particles.

[0075] The synthesized cerium oxide particles were dispersed so that the content thereof reached 0.1 wt %, and then a pH adjuster (acetic acid) was mixed to prepare a polishing slurry composition having a pH of 5.

[0076] Example 2

[0077] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 1, except that 0.1 M polyethylene glycol was used.

[0078] Example 3

[0079] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 1, except that 0.5 M polyethylene glycol was used.

[0080] Example 4

[0081] A trivalent cerium precursor (0.1 M) and polyethylene glycol (weight average molecular weight: 2000, 0.1 M) were added, and then an aqueous ammonia solution (0.3 M) was added, and the mixture was stirred at 900 rpm for 4 hours to synthesize cerium oxide particles.

[0082] The synthesized cerium oxide particles were dispersed so that the content thereof reached 0.1 wt %, and then a pH adjuster (acetic acid) was mixed to prepare a polishing slurry composition having a pH of 5.

[0083] Example 5

[0084] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 4 except that the stirring time was changed to 8 hours.

[0085] Example 6

[0086] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 4 except that the stirring time was changed to 12 hours.

[0087] Example 7

[0088] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 1, except that the nonionic compound was changed to polyglycerol (weight average molecular weight: 310, 0.1 M).

[0089] Example 8

[0090] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 1, except that the nonionic compound was changed to polyethylene (weight average molecular weight: 500, 0.1 M).

[0091] Example 9

[0092] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Example 1, except that the nonionic compound was changed to dextrin (0.1 M).

[0093] Comparative Example 1

[0094] A trivalent cerium precursor (0.1 M) and an aqueous ammonia solution (0.3 M) were added, and then stirred at 900 rpm for 4 hours to synthesize cerium oxide particles.

[0095] The synthesized cerium oxide particles were dispersed so that the content thereof reached 0.1 wt %, and then a pH adjuster (acetic acid) was mixed to prepare a polishing slurry composition having a pH of 5.

[0096] Comparative Example 2

[0097] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Comparative Example 1, except that the stirring time was changed to 8 hours.

[0098] Comparative Example 3

[0099] Cerium oxide particles were synthesized and a polishing slurry composition was prepared in the same manner as in Comparative Example 1, except that the stirring time was changed to 12 hours.

[0100] Comparative Example 4

[0101] A trivalent cerium precursor (0.1 M) and polyethyleneimine (weight average molecular weight: 610, 0.1 M) were added, and then an aqueous ammonia solution (0.3 M) was added, and the mixture was stirred at 900 rpm for 4 hours to synthesize cerium oxide particles.

[0102] The synthesized cerium oxide particles were dispersed so that the content thereof reached 0.1 wt %, and then a pH adjuster (acetic acid) was mixed to prepare a polishing slurry composition having a pH of 5.

[0103] Comparative Example 5

[0104] A trivalent cerium precursor (0.1 M) and polyacrylic acid (weight average molecular weight: 610, 0.1 M) were added, and then an aqueous ammonia solution (0.3 M) was added, and the mixture was stirred at 900 rpm for 4 hours to synthesize cerium oxide particles.

[0105] The synthesized cerium oxide particles were dispersed so that the content thereof reached 0.1 wt %, and then a pH adjuster (acetic acid) was mixed to prepare a polishing slurry composition having a pH of 5.

[0106] Evaluation of aggregation rate of cerium oxide particles

[0107] The cerium oxide particles were dispersed by ball milling, and the dispersion conditions were evaluated under the same conditions.

[0108] (1) The specific surface area of ​​the polishing particles was obtained by the BET (Brunauer-Emmett-Teller; BET) method, using nitrogen adsorption to obtain the isothermal adsorption curve of cerium oxide particles, and the specific surface area of ​​cerium oxide nanoparticles was calculated using the Langmuir formula. Then, the specific surface area calculated by BET was substituted into formula (2) to calculate the primary particle size. The results are shown in Tables 1 and 2.

[0109] (2) Secondary particle size: The particle size of the particles dispersed under the same grinding conditions was measured by the particle size analysis method using dynamic light scattering (DLS). The results are shown in Tables 1 and 2.

[0110] The aggregation rate was calculated by substituting the primary particle size and secondary particle size in Table 1 and Table 2 into Formula 1. The results are shown in Table 1 and Table 2.

[0111] [Formula 1]

[0112] A=[secondary particle size] / [primary particle size]

[0113] [Formula 2]

[0114]

[0115] In formula 1,

[0116] The primary particle size is r in formula 2, where r is the radius value and is used to calculate the diameter.

[0117] The secondary particle size is a value measured by a dynamic light scattering (DLS) method.

[0118] In formula 2, S0 is the specific surface area, r is the radius of the particle, and p is the density of the substance, which is substituted into 7.22.

[0119] Evaluation of zeta potential

[0120] The zeta potential of the polishing slurry composition was measured using a STABINO device. The results are shown in Tables 1 and 2.

[0121] Evaluation of polishing characteristics

[0122] Using the polishing slurry compositions of the examples and comparative examples, a substrate containing PETEOS was polished under the following polishing conditions.

[0123] [Polishing conditions]

[0124] (1) Polishing device: ST#01 (KCT)

[0125] (2) Carrier rpm: 60 / 63

[0126] (3) Wafer Pressure: 2psi

[0127] (4) Flow rate (ml / min): 200

[0128] (5) Pad: IC 1000

[0129] (6) Duration: 60 seconds

[0130] (7) R-ring pressure: 4.5 psi

[0131] In order to evaluate the polishing characteristics, the polishing slurry compositions of the examples and comparative examples were used to polish a PETEOS wafer substrate and then the polishing rates were measured. The results are shown in Table 1.

[0132]

Table 1

[0133]

[0134]

Table 2

[0135]

[0136] Referring to Tables 1 and 2, a polishing slurry composition is provided, which includes polishing particles having an aggregation ratio (Aggregate Ratio), i.e., a ratio of the primary particle size calculated by BET to the secondary particle size calculated by DLS method, between 1.5 and 2.5. Compared with the comparative examples outside this range, the polishing rate of the polishing object film is significantly improved.

[0137] In summary, the invention has been described by limited embodiments, and a person of ordinary skill in the art can make various changes and deformations based on the description. If the described techniques are performed in different orders, and / or if the described constituent elements are combined or combined in different forms, or replaced or substituted by other constituent elements or equivalents, appropriate results can also be obtained. Therefore, the scope of the invention is not limited by the embodiments, but by the claims and their equivalents, and all changes within the scope of the claims and their equivalents should be interpreted as included in the present disclosure.

Claims

1. A polishing slurry composition comprising cerium oxide polishing particles, characterized in that: The cerium oxide polishing particles include: Cerium; and Modifiers, The aggregation ratio A based on the following formula 1 is 1.5 to 2.5: [Formula 1] A=[secondary particle size] / [primary particle size] In Formula 1, the primary particle size is the diameter calculated from the r value of the following Formula 2, The secondary particle size is a value measured by a dynamic light scattering method; [Formula 2] In formula 2, S0 is the specific surface area, r is the radius of the particle, and p is the density of the substance; Wherein the primary particle size according to Formula 1 is 2 nm to 9.6 nm, The secondary particle size of the polishing particles is 10 nm to 40 nm, The molar ratio of the cerium element to the modifier is 1:0.1 to 1:1, wherein the modifier comprises at least one selected from the group consisting of polyethylene glycol, polyglycerol and dextrin, The polishing slurry composition has a positive zeta potential.

2. The polishing slurry composition according to claim 1, characterized in that The specific surface area of ​​the polishing particles is 31 m 2 / g or above.

3. The polishing slurry composition according to claim 1, characterized in that The density of the polishing particles is 6.7 g / cm 3 Up to 7.7g / cm 3 .

4. The polishing slurry composition according to claim 1, characterized in that The modifier is included in a concentration of 0.01M to 1M.

5. The polishing slurry composition according to claim 1, characterized in that The polishing particles are 0.01 wt % to 5 wt % of the slurry composition.

6. The polishing slurry composition according to claim 1, characterized in that Also included are pH adjusters.

7. The polishing slurry composition according to claim 6, characterized in that The pH adjuster includes an acidic substance, and the acidic substance includes at least one selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, nitrous acid, persulfuric acid, sulfurous acid, hyposulfurous acid, boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, superphosphoric acid, perchloric acid, chlorous acid, hypochlorous acid, bromic acid, bromous acid, hypobromous acid, perbromic acid, iodic acid, hypoiodous acid, periodic acid, hydrogen fluoride, boron trifluoride, tetrafluoroboric acid, hydrofluoric acid, formic acid, malonic acid, maleic acid, oxalic acid, adipic acid, citric acid, acetic acid, propionic acid, fumaric acid, salicylic acid, pimelic acid, benzoic acid, succinic acid, phthalic acid, butyric acid, glutaric acid, glutamic acid, glycolic acid, lactic acid, aspartic acid, tartaric acid, and their respective salts.

8. The polishing slurry composition according to claim 1, characterized in that The pH of the polishing slurry composition is 2 to 11.